Application of Morphological and Molecular Markers to Establish Distinctness in Few Genotypes of Yellow Sarson (Brassica rapa L. var. Yellow Sarson) - J BHAGAT; R PHUKAN; M BARUA; P SHARMA; AR BARUAH; RN SARMA; PK BARUA (Seed Research, 2024)
Yellow sarson, a self-pollinated ecotype of rapeseed (Brassica rapa L.), is an important oilseed crop of India for use as an oilseed and as a condiment. This study was an attempt to characterize five genotypes of yellow sarson including three varieties (B9, YSH401, Pitambari) and two elite breeding lines (AAUJYS14-2 and AAUJYS15-2) by morphological characters as per DUS test guidelines and by molecular markers. Of the 24 morphological descriptors, genotypic differences were observed for 14 characters viz., leaf hairiness, leaf colour, leaf length, leaf width, plant height, main shoot length, days to flowering, days to maturity, siliqua angle, siliqua beak length, number of seeds per siliqua, siliqua density, 1000 seed weight and oil content. Mahalanobis D2 analysis revealed that the genotypes were grouped individually into five equidistant solitary clusters. Molecular analysis was carried out by 20 random simple sequence repeats (SSR) primers, of which 12 primers turned out to be polymorphic. PIC value ranged from 0.2 to 0.96 with an average of 0.47. Broadly two clusters were formed based on Jaccard’s coefficient of similarity. Cluster A was divided into two sub-clusters, AI (YSH401, AAUJYS15- 2) and AII (B9). Cluster B included Pitambari and AAUJYS14-2. Thus, the use of molecular markers in conjunction with morphological descriptors could be useful for plant variety characterization and for establishing distinctness of varieties that enter the seed multiplication chain.